Analisa Keruntuhan Bendungan Gondang Dengan Menggunakan Program Zhong Xing HY21 - Aryadi, Eric Virgiawan; Juwono, Pitojo Tri; Priyantoro, Dwi; Asmaranto, Runi (Fakultas Teknik, Universitas Brawijaya, 2014)
Dam failure occured due to overtopping and piping. This can lead to rapid propagatioin of water flow so inundated the downstream of the dam. The purpose of this study was to analyze the various scenarios for the dam break. Dam Break Analysis conducted with Zhong Xing HY21 software. This study conducted the dam break analysis with overtopping and piping scenarios by insterting certain fracture parameters in order to obtain the outflow hydrograph.Gondang Dam Break greatest impact if experienced overtopping with Q Inflow 968,548 m /sec and produce Q Outflow 7671,57 m /sec. Result flood routing water level of the reservoir was located at an elevation of +40,593 (Gondang Dam Crest Elevation +42,00), so assumed the dam crest elevation of + 40,00. This flood could be trace Gondang River and flooded rice field and also the settlement area around Â±73 km 2 . 3Keyword: Dam, Overtopping, Piping, Dam Break Analysis, ZhongXing HY21